Service quality models in the public drinking water supply in Mexico - Silva, Jorge (Tecnología y ciencias del agua, 2025)
To analyze service quality models in the public drinking water supply in Mexico. The paper conducts a systematic review of various works of erudition on the subject, with the models being identified based on their application. A systematic literature review was conducted using the Preferred Reporting Item for Systematic Reviews (PRISMA) and the 3-stage approach by Arksey and O’Malley. The study design was chosen because it helps in the identification of articles through predefined criteria. Electronic searches were conducted via Web of Science and Scopus, with articles published between 1980 and 2022 being identified. The articles were then screened for relevance, applicability, validity, and reliability. The review identified at least five GAPS under the GAP model, which include knowledge, policy, delivery, communication, and consumer. Subsequently, the SERVQUAL model shows that the public drinking water supply systems fall below the set expectations of reliability, assurance, empathy, tangibles, and responsiveness. Contrarily, the government has set up programs like PROME and the Citizens’ Initiatives for General Water Law aimed at improving citizen participation and comprehension of key GAPS in the water supply system. The research is novel as it prods the subject of service quality models in Mexico. This topic is an unexplored area, especially with regard to the GAP and SERVQUAL models. The insight derived from this paper will bridge the existent dearth of knowledge while improving policy formulation and implementation.